อนาคตภาพรูปแบบค่ายวิทยาศาสตร์เพื่อการเรียนรู้ตลอดชีวิตในยุคดิจิทัล - วสุ ทัพพะรังสี (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The future research approach is applied from Ethnographic Delphi Future Research (EDFR). The aims are to 1) analyze and synthesize principle and concept of science camp model towards lifelong learning in digital age 2) develop the scenario of science camp model towards lifelong learning in digital age and 3) present the scenario of science camp model towards lifelong learning in digital age. The research was conducted through the related documentaries and the exploration of 27 experts’ perspectives. In-depth interview, focus group, and probable trends of the scenario of science camp model towards lifelong learning in digital age were used as methodologies. The research findings are as follows: 1. The analysis and synthesis of principles and concepts of science camp model towards lifelong learning in digital age have shown that the related principles enhancing science learning, non – formal education, impelling people and social to lifelong learning, and preparing citizen for life in digital age. The concepts associated with organizing science camp model towards lifelong learning in digital age consist of varieties of learning management that support learning for scientific process skill, digital technology skill including lifelong learning. 2. The scenario of science camp model towards lifelong learning in digital age consist of six main elements, e.g., Strategic Management, Management Structure, Knowledge Service Pattern, Science Camp Curriculum and Curriculum Management, Quality Accreditation, and Network. 3. The trend of the scenario of science camp model towards lifelong learning in digital age comprise four science camp options, such as, option 1) Unavailable Digital – Inability Users: science camp model that lacks accessibility by neither digital technology nor teacher and learner, option 2) Unavailable Digital - Readiness Users: science camp model that lacks accessibility to digital technology despite the readiness of teacher and learner, option 3) Available Digital – Inability Users: science camp that lacks accessibility by teacher and learner despite convenient digital technology, and option 4) Available Digital – Readiness Users: science camp model having both digital technology and teacher and learners.